A Qualitative Study of Yiddish-Speaking Hasidic Mothers' Experiences Parenting Deaf and Hard of Hearing Children. - Rosenzweig, Elizabeth A.; Ganek, Hillary V.; Jolivette, Jonathan; Tessler, Madison (Journal of Speech, Language & Hearing Research, 2026)
Purpose: The current study presents the results of a qualitative investigation into the perspectives and experiences of Yiddish-speaking Hasidic Jewish mothers of children who are deaf and hard of hearing. Method: Six mothers, recruited via convenience and snowball sampling, participated in semistructured interviews in person or via phone. The interviews were transcribed and coded for thematic analysis. Results: Identified themes fell under the umbrella of "relationships," including language, professionals, community, and family. Conclusion: Based on the thematic analysis of the participants' responses, key themes and implications for professional practice are proposed, such as the importance of culturally responsive practice, understanding the unique counseling needs of this population (particularly regarding genetic testing and educational placement), and considerations regarding technology use.